On Some Characters in the Kazakh National Heroic Epic “Kobyland Hero” - Baygabil, Riza (Studia Folclorica, 2025)
This study delves into the portrayal of selected characters from Kobyland, the most widely disseminated and monumental heroic epic of the Kazakh people. Scholars regard this epic as originating in the 15th century, and to date, twenty-nine versions of Kobyland have been identified. This study explores the symbolic attributes and narrative functions of Kobyland and queen Kurtka within the epic tradition. The epic of Kobyland is characterized by having fewer mythical elements and more realistic depictions of events, making it notable as a historical epic. Through this epic, one can discern the defining qualities of the Kazakh hero, queen, and wife including steadfast loyalty in love, the virtues of womanhood, and the sacred bond of sworn brotherhood. Казах үндэстний “Кобыланд баатар” баатарлагийн туульсын зарим дүрийн тухайд Хураангуй: Казах үндэстний “Кобыланд баатар” баатарлагийн туулийн зарим дүрийн тухай тууль дахь дүрслэлээс жишээлэн авч, орчуулан тайлбарлажээ. Энэ дүрслэлээс казах баатарлаг туулийн онцлог, тухайн үндэстний соёл энэхүү туульд хэрхэн илэрсэн, ёс уламжлал, туульд дүрслэгдсэн зан заншил, уламжлал нь өнөө цагт хэрхэн хадгалагдсан болон устаж үгүй болсныг ажиглаж болно. Үүнээс гадна тухайн дүрээр дамжуулан казах түмний эр хүн, эхнэр хүнийг үзэх үзэл, андын тангаргийн талаар авч үзэв. Түлхүүр үг: Казах тууль, Кобыланд дүрийн судалгаа, баатарлаг тууль, ёс уламжлал